A Development-Associated Decrease in Osmotic Potential Contributes to Fruit Ripening Initiation in Strawberry (Fragaria ananassa) - Jia, Kenan; Zhang, Qing; Xing, Yu; Yan, Jiaqi; Liu, Luo; Nie, Kaili (Frontiers in Plant Science, 2020)
Fruit development and ripening are accompanied by a large increase in cellular soluble solid contents, which results in a significant decrease in osmotic potential (DOP). Here, we report that this development-associated DOP contributes to the initiation of ripening in strawberry (Fragaria ananassa Duch., Benihoppe) fruit. We show that fruit water potential significantly decreases at the onset of ripening as a result of the DOP. Further analysis using nuclear magnetic resonance spectroscopy (NMR) indicated that the change in fruit water potential was likely caused by catabolism of large molecules in receptacle cells, and bioinformatic analysis identified a family of osmotin-like proteins (OLP) that have a potential role in osmolyte accommodation. The gene expression of more than half of the OLP members increased substantially at the onset of fruit ripening, and specifically responded to DOP treatment, consistent with a close relationship between DOP and fruit ripening. We report that the DOP induced either by mannitol or water loss, triggered fruit ripening, as indicated by the elevated expression of multiple ripening genes and diverse ripening-associated physiological parameters. Collectively, these results suggest that the DOP contributes to strawberry fruit ripening initiation.